PFS24 as a prognostic milestone in patients with newly diagnosed primary CNS lymphoma - Vanja Zeremski; Tobias R. Haage; Hanno M. Witte; Louisa Adolph; Sina A. Beer; Gerhard Behre; Benedikt Jacobs; Christoph Kahl; Chrysavgi Lalayanni; Jens Panse; Sotirios Papageorgiou; Marina P. Siakantaris; et al. (Journal of Hematology & Oncology)
Abstract High-dose chemotherapy followed by autologous hematopoietic stem cell transplantation has significantly improved overall survival (OS) in primary central nervous system lymphoma (PCNSL). However, early identification of long-term survivors remains a challenge. Progression-free survival at 24 months (PFS24) has emerged as a key prognostic marker in diffuse large B-cell lymphoma, but its relevance in PCNSL is still unclear. In this retrospective multicenter study, we analyzed data from 146 newly diagnosed, transplant-eligible PCNSL patients treated with MATRix-like regimens across 14 hospitals. With a median follow-up of 48 months, the 2-year PFS and OS rates were 50.4% and 65.6%, respectively. Of the 139 patients evaluable for PFS24-analysis, 51.1% reached PFS24, with a subsequent 5-year OS of 96.7%. Of note, the annual hazard rate for progression and death decreased to under 5% after 24 months, remaining stable thereafter. The patients who failed to reach PFS24 had a median OS of only 6.0 months. Key predictors of PFS failure included impaired Karnofsky performance status and treatment dose-reduction. In conclusion, PFS24 was identified as an important prognostic marker in PCNSL. Patients who achieve PFS24 have a favorable prognosis, whereas those who do not face poor outcomes and require innovative treatment approaches. This insight could aid in risk stratification and support the use of PFS24 as a surrogate endpoint in clinical trials.